2002
DOI: 10.1103/physrevlett.89.116802
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of Interacting Composite Fermions in the Bilayerν=2/3Quantum Hall Effect

Abstract: We study the phase diagram of composite fermions (CFs) in the presence of spin and pseudospin degrees of freedom in the bilayer nu=2/3 quantum Hall (QH) state. Activation studies elucidate the existence of three different QH states with two different types of hysteresis in the magnetotransport. While a noninteracting CF model provides a qualitative account of the phase diagram, the observed renormalization of tunneling gap and a non-QH state at high densities are not explained in the noninteracting CF model, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…III) By applying a voltage bias as described above, they perform four sweeps in the d, ∆ SAS plane. In one sweep [46] they find a seemingly first-order transition at d/ℓ B ≈ 2, ∆ SAS / e 2 ǫℓB ≈ 0.1. This sweep, and the location of the observed transition, are shown in Fig.…”
Section: Experimental Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…III) By applying a voltage bias as described above, they perform four sweeps in the d, ∆ SAS plane. In one sweep [46] they find a seemingly first-order transition at d/ℓ B ≈ 2, ∆ SAS / e 2 ǫℓB ≈ 0.1. This sweep, and the location of the observed transition, are shown in Fig.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…Also note that experimental studies [46,85] on this system have observed a spin-polarized system at all the tunneling strengths and interlayer separations accessed, for magnetic fields B ≈ 4-11 T.…”
Section: Spin Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9] Resistively -detected nuclear magnetic resonance measurements have shown the involvement of the nuclear spin polarization in the origin of the R xx peak.…”
Section: -4)mentioning
confidence: 99%